2011
DOI: 10.1038/ki.2011.123
|View full text |Cite
|
Sign up to set email alerts
|

Early postoperative serum cystatin C predicts severe acute kidney injury following pediatric cardiac surgery

Abstract: In this multicenter, prospective study of 288 children (half under 2 years of age) undergoing cardiac surgery, we evaluated whether the measurement of pre- and postoperative serum cystatin C (CysC) improves the prediction of acute kidney injury (AKI) over that obtained by serum creatinine (SCr). Higher preoperative SCr-based estimated glomerular filtration rates predicted higher risk of the postoperative primary outcomes of stage 1 and 2 AKI (adjusted odds ratios (ORs) 1.5 and 1.9, respectively). Preoperative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
80
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 121 publications
(89 citation statements)
references
References 24 publications
8
80
1
Order By: Relevance
“…In TRIBE-AKI, we found that using a simple baseline clinical risk model, including age, gender, RACHS-1 category, preoperative eGFR percentile, CPB time, and study site, predicted postoperative AKI with AUC 0.77 and was improved by adding biomarkers to this model. 36 Similar risk models may help to increase the specificity and positive predictive value of biomarker screening tests. 58 Before the use of these biomarkers can be incorporated into routine clinical practice, however, AKI prevention strategies must be have confounded the relationship between cardiac biomarkers and postoperative AKI.…”
Section: Discussionmentioning
confidence: 99%
“…In TRIBE-AKI, we found that using a simple baseline clinical risk model, including age, gender, RACHS-1 category, preoperative eGFR percentile, CPB time, and study site, predicted postoperative AKI with AUC 0.77 and was improved by adding biomarkers to this model. 36 Similar risk models may help to increase the specificity and positive predictive value of biomarker screening tests. 58 Before the use of these biomarkers can be incorporated into routine clinical practice, however, AKI prevention strategies must be have confounded the relationship between cardiac biomarkers and postoperative AKI.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 In recent years, several studies have shown that novel biomarkers can detect acute tubular injury earlier than serum creatinine in the setting of AKI. [7][8][9][10][11] Despite attempts to select patients at high risk for severe AKI, the majority of patients in these prospective studies do not develop clinical AKI. Additionally, most of those patients who develop AKI experience a milder form of AKI (e.g., AKIN stage 1 or RIFLE R) with transient bumps in serum creatinine and do not progress to more severe AKI stages (AKIN stage 2 or 3 or RIFLE F) or require acute dialysis.…”
mentioning
confidence: 99%
“…The accuracy of urine IL-18 and urine NGAL for diagnosis of severe AKI was moderate, with AUCs of 0.72 and 0.71, respectively. In this pediatric cohort, none of the quintiles of plasma NGAL were independently associated with the development of postoperative severe AKI (19 (22).…”
Section: Postoperative Biomarkersmentioning
confidence: 99%
“…Many of these previously published studies are limited in that they are small single-center studies with low severe AKI event rates (10)(11)(12)(13)(14)(15)(16)(17). However, within the last year, data from the first large international, prospective observational study investigating biomarkers after cardiac surgery have been published (18)(19)(20)(21)(22). The Translational Research Investigating Biomarker Endpoints in AKI (TRIBE AKI) study assembled a cohort of 1219 adults undergoing coronary artery bypass grafting and/or valvular surgery cardiac surgery and 311 children undergoing surgery for congenital cardiac lesions.…”
Section: Aki Associated With Cardiac Surgerymentioning
confidence: 99%